Melting heat transfer of a non-Newtonian phase change material in a cylindrical vertical-cavity partially filled porous media. Issue 7 (28th November 2019) - Ghalambaz, Mohammad; Ayoubi Ayoubloo, Kasra; Hajjar, Ahmad
Abstract : Purpose: This paper aims to investigate melting heat transfer of a non-Newtonian phase change material (PCM) in a cylindrical enclosure-space between two tubes using a deformed mesh method. Design/methodology/approach: Metal foam porous layers support the inner and outer walls of the enclosure. The porous layers and clear space of the enclosure are filled with PCM. The natural convection effects during the phase change are taken into account, and the governing equations for the molten region and solid region of the enclosure are introduced. The governing equations are transformed into non-dimensional form and then solved using finite element method. The results are compared with the literary works and found in good agreement. The non-Newtonian effects on the phase change heat transfer and melting front are studied. Findings: The results show that the increase of non-Newtonian effects (the decrease of the power-law index) enhances the heat melting process in the cavity at the moderate times of phase change heat transfer. The temperature gradients in porous metal foam over the hot wall are small, and hence, the porous layer notably increases the melting rate. When the melting front reaches the cold porous layer, strong non-linear behaviors of the melting front can be observed. Originality/value: The phase change heat transfer of non-Newtonian fluid in a cylindrical enclosure partially filled with metal foams is addressed for the first time.